1992
DOI: 10.1039/jm9920200595
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous aluminosilicates: preparation from Ca-A zeolite by treatment with ammonium fluorosilicate

Abstract: Ammonium hexafluorosilicate (AFS) in aqueous solution under mild conditions can modify drastically the textural properties of Ca-A zeolite. Open slit-shaped mesopores with a pore-size distribution showing a maximum at 14-20nm are formed. The average pore diameter depends on the rate of addition of the AFS solution to the leaching medium. If such a treatment is combined with acid leaching or hydrothermal treatment, the mesoporous materials obtained exhibit similar pore-size distribution. However, their adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…When zeolite Y was dealuminated by SiCl 4 , little mesoporosity was generated and most of the microporosity of the zeolite was preserved . Le Van Mao et al showed that the textural and adsorptive properties of Ca-A zeolite undergo significant changes upon mild leaching, controlled hydrothermal treatment, or chemical treatment with AFS . Aqueous AFS solution, under mild conditions (e.g., room temperature, pH ≈ 7.0), created slit-shaped mesopores with a distribution maximum at 14−20 nm; the average pore diameter depends on the rate of addition of the AFS solution to the leaching medium.…”
Section: 2 Hydrothermal and Chemical Treatmentsmentioning
confidence: 99%
“…When zeolite Y was dealuminated by SiCl 4 , little mesoporosity was generated and most of the microporosity of the zeolite was preserved . Le Van Mao et al showed that the textural and adsorptive properties of Ca-A zeolite undergo significant changes upon mild leaching, controlled hydrothermal treatment, or chemical treatment with AFS . Aqueous AFS solution, under mild conditions (e.g., room temperature, pH ≈ 7.0), created slit-shaped mesopores with a distribution maximum at 14−20 nm; the average pore diameter depends on the rate of addition of the AFS solution to the leaching medium.…”
Section: 2 Hydrothermal and Chemical Treatmentsmentioning
confidence: 99%
“…In order to retain the crystal structure of dealuminated zeolite crystal, the post dealumination can also be carried out in aqueous solutions containing ammonium hexafluorosilicate [20,21] and SiCl 4 [22][23][24]. This can heal the dealuminated framework sites with silicate species during the dealumination treatment.…”
Section: Post-synthetic Demetallation Of Zeolite Crystalsmentioning
confidence: 99%
“…In this route, the mesopores can be produced by base treatment that can leach out the Si species from the zeolite framework, which makes mesopores that are interconnected each other and accessible from the external surface of the zeolite crystal [26,27]. The desilication process is effective for high-silica zeolites (usually Si/Al [ 20) than high Al zeolites [28,29]. It was reported that mesoporous textures generated by the desilication process strongly depend on the concentration and distribution of Al within the zeolite crystals [26,28,30].…”
Section: Post-synthetic Demetallation Of Zeolite Crystalsmentioning
confidence: 99%
“…[4][5][6][7]12]. The basic procedure was as follows: 2.7 g of NaX or 5.0 g of CaA zeolite (all in powder form) were placed into a Teflon beaker containing 200 cm 3 of 0.8 mol dm )3 ammonium acetate solution (pH of ca.…”
Section: Controlled Dealumination Of Nax and Caa Zeolitesmentioning
confidence: 99%
“…Unfortunately, these materials are known to be quite thermally and chemically unstable [3]. In the past, we have shown that mesoporous materials can be obtained from Al-rich zeolites by controlled dealumination using ammonium hexafluorosilicate (AHFS) as Al removing agent [4][5][6][7]. This is in contrast with more aggressive Al removing media such as mineral acids which usually lead to severe structural collapses and thus not very useful mesoporous materials because the latter are subject to numerous pore occlusions [8] or a lack of direct connection with the external surface of the treated zeolite particle [9].…”
Section: Introductionmentioning
confidence: 99%